Acute pancreatitis after gastro-jejunal tube placement in patient with severe scoliosis - Yasushi Iinuma; Yutaka Hirayama; Kengo Nakaya; Yu Sugai; Shotaro Taki; Shin-ichi Naito; Ko Matsui; Hiroki Kurosawa; Tetsuya Otani (Elsevier, 2021)
We herein report a 14-year-old cerebral palsy patient with severe scoliosis who developed acute pancreatitis, just after the insertion of a gastro-jejunal tube (GJT) to carry out jejunal feeding. The patient underwent laparoscopic fundoplication and gastrostomy as a treatment for gastroesophageal reflux disease. After surgery, the patient developed leakage and gastrostomy feeding difficulty overtime, subsequently, GJT feeding through an established gastrostomy was initiated.However, the patient developed acute pancreatitis two days after the insertion of a GJT. Computed tomography showed peri-pancreas massive edema and that duodenum had become apparently displaced due to the patient's pre-existing scoliosis. Furthermore, it looked like that the direct compression to the whole pancreas had possibly been occurred by the inserted GJT. The occurrence of GJT related pancreatitis was suspected, and subsequently, the pancreatitis improved after the removal of the GJT. The patient thereafter underwent gastro-jejunal bypass surgery. A GJT is a useful device for jejunal feeding which can be inserted from an established gastrostomy, however, its usage should be limited because of a high rate of morbidity. In patient with cerebral palsy, especially combined with severe scoliosis, we should recognize that the insertion of GJT can cause acute pancreatitis due to the risk of direct compression to the patient's pancreas by the GJT.